Winning : reflections on an American obsession - Duina, Francesco G., 1969- (Princeton University Press, 2011)
"Most of us are taught from a young age to be winners and avoid being losers. But what does it mean to win or lose? And why do we care so much? Does winning make us happy? Winning undertakes an unprecedented investigation of winning and losing in American society, what we are really after as we struggle to win, our collective beliefs about winners and losers, and much more. The author argues that victory and loss are not endpoints or final destinations but gateways to something of immense importance to us: the affirmation of our place in the world. But he also shows that competition is unlikely to provide us with the answers we need. Winning and losing are artificial and logically flawed concepts that put us at odds with the world around us and, ultimately, ourselves. He explores the social and psychological effects of the language of competition in American culture. Primarily concerned with our shared obsessions about winning and losing, this work proposes a new mind set for how we can pursue our dreams, and, in a more satisfying way, find our proper place in the world"--Provided by publisher.